URBAN POVERTY ANALYSIS IN TAMALE, GHANA - Damba, O. T.; Abarike, M. A.; Nabilse, C. K.; Akudugu, M. A. (UDS International Journal of Development, 2019)
Traditionally, much of the analysis of poverty has been on rural areas, but little attention is paid to urban poverty. Poverty is a huge concern among urban dwellers due to an average monthly income of GHS150 with an exorbitant basket of expenditure. Urban poverty is exacerbated by the lack of social capital coupled with increasing utility tariffs with a translated cost in production and processing activities. Urban poverty has a gender dimension due to the male - dominated household roles coupled with low or lack of assets’ control by women. This has worsened the poverty situation among households as expenses are borne by males as head of the household. Poverty in urban Sagnarigu and Tamale is based on a lack of money or inability to meet basic household needs. Urban dwellers consider unemployment as poverty but still consider living in urban areas better compared to rural areas due to the availability of basic amenities such as toilets, access to portable drinking water and electricity. Safety net programmes and interventions are the remedies of urban poverty, which are largely concentrated in the rural areas. Emphasis on education is required especially among females since there is a cultural shift of emphasis to petty trading as a quick source of money. This has caused a further gap in girl-child education and by extension, adult literacy improvement. Keywords: Urban Migration Poverty, Multidimensional Poverty Index, Tamale Metropolis, Sagnarigu District